Social problems and the quality of life - Robert H. Lauer (New York : McGraw-Hill Education, 2019)
This book is organized around the theme of the quality of life. It seeks to define what a social problem is and then addresses specific issues: How can one gain a sociological understanding of social problems? What kinds of critical thinking should one engage in and what kinds should one avoid in attempting to understand social problems? How is the quality of one$1 (Bs life affected by particular problems? What causes these problems and how can we resolve them? In Part One, the authors lay the groundwork by establishing key approaches to social problems. In the remaining sections, they discuss the social problems that most acutely influence our lives, and examine each problem for its impact on the quality of our lives.s
Keywords: Quality of life; Social conditions; Social problems